Modeling molten droplet spreading and infiltration into non-isothermal thermal barrier coatings. (January 2022) - Munuhe, Timothy W.; Chen, Ruey-Hung; Zhu, Liang; Ma, Ronghui
Highlights: An integrated model is introduced incorporating simultaneous droplet spreading, wetting interactions, heat transfer, and liquid infiltration with temperature-dependent viscosities in unsaturated porous media. This study shows that CMAS droplets of a size encountered by real gas turbines will lose their initial thermal energy soon after impact on a TBC and have negligible influence on the overall infiltration behavior. The temperature gradient within the TBC topcoat has a substantial impact on the CMAS infiltration rate. An anisotropic microstructure can significantly affect the lateral spreading and final penetration depth but has an insignificant influence on the initial infiltration rate. Heterogeneous structures such as bilayer and multilayer structures can limit and delay vertical infiltration by diminishing the vertical pressure gradient and increasing the resistance to fluid flow. Abstract: Molten calcium-magnesium-alumino-silicate (CMAS) droplets impact and infiltrate porous thermal barrier coatings (TBCs) of gas turbines, thereby causing loss of strain tolerance and delamination of the ceramic topcoat. To develop efficient mitigation strategies, it is crucial to understand CMAS infiltration dynamics into the porous topcoat. An integrated model is introduced incorporating simultaneous droplet spreading, wetting interactions, heat transfer, and liquid infiltration with temperature-dependent viscosities in unsaturated porous media. The model is applied to CMAS droplet interactions with homogeneous/heterogeneous anisotropic TBC topcoats grown by the electron beam physical vapor deposition (EB-PVD) method. Simulation results show that the droplet height and contact diameter dynamics exhibit three stages - initial-stage fast decrease, slow quasi-linear intermediate decrease, and late-stage fast decrease. The first two stages are dominated by the dynamics of infiltration. The initial temperature of the droplet has insignificant effect on the infiltration dynamics. Rather, the temperature gradient in the topcoat is critical to the infiltration rate. The anisotropy determines the final infiltration diameter and depth. Further, bilayer and multilayer coating structures with alternating fine and coarse columns can delay the infiltration rate and promote lateral spreading during the early stage of the droplet infiltration compared to single-layer structures. The results demonstrate that heterogeneous structures provide a viable approach to mitigate fast infiltration and reduce damage to the TBCs during the early stage of droplet infiltration.